Population Analysis (Total Weight, CaCO3 Total Weight and Segment Numbers) of Halimedaopuntia (Linn.) Lamouroux in Tongkeina Waters, Manado - Parera, Kristianto; Kepel, Rene Charles; Kambey, Alex D. (Jurnal Ilmiah PLATAX, 2015)
This study were aiming to know the biological aspects of H. opuntia in term of its total wet weight, CaCO3total weight and segment numbers and relationship of segment numbers with total weight (wet and CaCO3 content). Data collection was conducted in June, 2015 and samples were taken during the day light during the low tides. Line transect and quadrate of 1 x 1 meter were used in this study. In total there are 3 line transects of50 meter in length with 25 meter distant apart of each transect and were deployed perpendicular toward coastal line. To reveal the variation on total wet weight, CaCO3 wet content and segment numbers the data were plotted on bar diagram. The regression analysis and analysis of variance also were used to reveal the relationship among the parameters measured. The result of the study are as follow:  total individuals are 215 with composition of 76 individuals in transect 1; 66 individuals in transect 2 and 73 individuals in transect 3; total wet weight: 1,259.429 gram;  total weight of CaCO3: 354.551 gram; and segment numbers 82.580. The result of regression analysis shows that there is a strong relationship between number of segment and CaCO3 wet content. Keyword : Population Analysis, Halimeda opuntia   ABSTRAK   Tujuan dari penelitian ini adalah untuk mengetahui berat basah total, berat kapur total dan  jumlah segmen total serta hubungan jumlah segmen total dengan berat basah total dan hubungan jumlah segmen total dengan berat kapur total dari Halimeda opuntia. Penelitian ini dilakukan di perairan Tongkaina Kota Manado pada bulan Juni 2015.  Pengambilan sampel dilakukan pada siang hari pada saat keadaan air laut surut dengan menggunakan metode transek dan kuadrat dengan ukuran 1 x 1 meter.  Pengambilan sampel dibagi atas 3 transek dengan masing-masing transek terdiri dari 10 kuadrat dengan panjang transek masing-masing 50 m, jarak antara transek dengan lainnya 25 m dan jarak antara titik kuadrat dengan lainnya 5 m. Untuk melihat variasi ukuran berat basah total, jumlah segmen total dan berat kapur total pada sampel dari lokasi penelitian tersebut, maka dibuat diagram batang, analis hubungan dan analisis keragaman.  Hasil penelitian diperoleh 215 individu masing-masing 76 individu (transek 1), 66 individu (transek 2) dan 73 individu (transek 3).  Jumlah berat basah total yang dihitung adalah 1.259,429 gram, berat kapur total  354,551 gram dan jumlah segmen total 82.580 segmen. Hasil analisis regresi hubungan jumlah segmen menunjukan bahwa hubungan kedua variabel tersebut memiliki hubungan yang sangat kuat dan analisis regresi hubungan jumlah segmen total dan berat kapur total memiliki hubungan yang kuat. Kata kunci: Analisis Populasi, Halimeda opuntia 1Mahasiswa Program Studi MSP FPIK-UNSRAT 2Staf pengajar Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi